Equine rotavirus a under the one health lens : potential impacts on public health - Carossino, Mariano (2024)
Group A rotaviruses are a well-known cause of viral gastroenteritis in infants and children, as well as in many mammalian species and birds, affecting them at a young age. This group of viruses has a double-stranded, segmented RNA genome with high genetic diversity linked to point mutations, recombination, and, importantly, reassortment. While initial molecular investigations undertaken in the 1900s suggested host range restriction among group A rotaviruses based on the fact that different gene segments were distributed among different animal species, recent molecular surveillance and genome constellation genotyping studies conducted by the Rotavirus Classification Working Group (RCWG) have shown that animal rotaviruses serve as a source of diversification of human rotavirus A, highlighting their zoonotic potential. Rotaviruses occurring in various animal species have been linked with contributing genetic material to human rotaviruses, including horses, with the most recent identification of equine-like G3 rotavirus A infecting children. The goal of this article is to review relevant information related to rotavirus structure/genomic organization, epidemiology (with a focus on human and equine rotavirus A), evolution, inter-species transmission, and the potential zoonotic role of equine and other animal rotaviruses. Diagnostics, surveillance and the current status of human and livestock vaccines against RVA are also reviewed.